Jihad Dan Terorisme - Efendi, Zul (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2013)
The word jihad in Al-Qur'an in the general sense in the aim to proclaim Islam. Or jihad for what is generally used as an effort to uphold the truth and fight against crime, such as carrying out God destroy the tyranny of religious teachings, including apostasy and jihad against infidels. Everything is done for God expect subside. This is the jihad of people who believe. The term terrorist by counterterrorism experts said referring to the perpetrators who are not members of the armed forces are known or did not follow the rules armed forces. Terrorism also implies that attacking terrorist acts carried out inhuman and has no justification, and therefore the perpetrators (â€œterroristsâ€) deserve a vicious retribution a. That the jihad that is spilling all the ability to enforce the truth and destroy falsehood, it is the duty of every Muslim. And jihad infidel must fend terkomando organized and, as has been done in the war era, the Prophet Muhammad and now by amri ulil. b. Muslims who do jihad own with no permit ulil amri named Khawarij (terrorism) that must be fought, because they interfere with other Muslims. And usage to Osama bin Ladenâ€™s jihad is appropriate because he defend Islam and to defend themselves from attack Amerikan and its allies and Imam Samudra are suitable sekali.dianggab jihad is not terrorism because according to Islamic rules.